CONGENITAL NEPHROTIC SYNDROME: A CASE REPORT - Dr. ERNI MURDANINGSIH; Dr. SYARIFUDDIN RAUF; Dr. JUSLI ARAS (International Journal of Multidisciplinary Research and Studies, 2022)
Congenital nephrotic syndrome (CNS) is a rare kidney disorder characterized by severe protein urea, hypo-protein aemia, and edema commencing shortly after birth. The majority CNS type often discovered is Finnish by common indication of prematurely born infant with a large placenta. Prenatal diagnosis can be through the detection of high levels of Alfa fetoprotein in the amniotic fluid. The infant aged one month 18 days had abdominal swelling that was noticeable from 21 days after birth. The infant hospitalized at Kolaka Hospital had anasarca edema, hypo-albuminemia (albumin 1.0 g / dl), protein urea (+++), and hyper-lipidaemia (209). Patient’s history of receiving albumin transfusions. Referring to the anamnesis and physical examination, the infant endured a CNS started less than three months after birth, and the onset factor of symptoms led to primary CNS due to genetic disorders. The diagnosis is made based on history, physical examination, and supporting investigations. The patient accepts the treatment of intravenous albumin transfusion followed by intravenous antibiotics for secondary infection.